Comparative study of structure and photo-induced reactivity of malonaldehyde and acetylacetone isolated in nitrogen matrices: Molecular Solids - Trivella, A.; Coussan, S.; Chiavassa, T.; Theulé, P.; Manca, C.; Roubin, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Structure and reactivity of the eight enolic forms (one chelated and seven non-chelated) of malonaldehyde and acetylacetone are compared through theoretical and experimental data.Ground-state geometries, energies, and vibrational frequencies are calculated with the B3LYP/6–311++G(2d, 2p) model chemistry. The electronic delocalisation as well as the cis/trans rotamer properties are analysed. The hydrogen bond strength of the chelated forms canbe estimated by the energy difference between chelated and non-chelated forms, and its enhancementdue to methyl-induced electron release is estimated at 1.7 kcal·mol–1. UV- and IR-induced reactivity of molecules isolated in nitrogen matrices is studied by means of FT–IRspectrometry. Interconversion between rotamers is the main process observed for both molecules,only some among the seven non-chelated forms being created.